FREEMARTINISM IN DAIRY ANIMALS – AN ANALYSIS OF SIX CASES - Shukla , M K; Siddiquee , G M (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
Six cases of freemartins presented to the Teaching Veterinary Clinical Service Complex, Sardarkrushinagar were examined and diagnosed. The freemartins are a sterile female born as co-twin to a male calf and rarest cases of this condition are encountered in veterinary practice and hence these six cases are placed on records.